A case of post-COVID-19 fibrosis mimicking Thoracic Manifestation of Ankylosing Spondylitis. - Doğan, Emrah; Olcay, Sabri Serhan; Çınar Olcay, Tuba; Tapan, Utku; Tapan, Ozge Oral; Alaşan, Fatih (Acta medica Lituanica, 2022)
The most common thoracic manifestation form of ankylosing spondylitis is apical fibrocystic changes. It is also known as apical fibrobullous disease (AFBD). The patient was diagnosed with ankylosing spondylitis before 9 years. He suffered COVID-19 infection and passed an intensive care period. However, post-covid fibrosis (PCF) atypically affected dominantly apical zones. If we had no sequential CT evaluations, our case could be easily confused with AFBD. On CT taken before COVID-19, the lung apex was normal. Thus, it was confirmed that there was no rheumatologic thoracic manifestation in the patient before suffering from COVID-19 pneumonia. PCF created similar changes as AFBD. Our case is the first reported paper on this topic.
Keywords: Ankylosing spondylitis; Post-covid fibrosis; Apical fibrobullous disease; Computed tomography